STILISTIKA PADA WACANA INSTAGRAM-ADS HOTEL KAYON RESORT - Ni Putu Isha Aprinica; Luh Eka Susanti; Ketut Muliadiasa (STKIP PGRI Jombang, 2022)
Advertising is part of the communication process in which the components contained in the advertisement are in the form of sentences as a form of language style commonly found in society. Kayon Resort is located on the hillside of Ubud, surrounded by the sacred Petanu River and lush tropical rainforest providing a relaxing atmosphere. The purpose of this study was to determine the meaning and stylistics of the Kayon Resort Ubud hotel advertisement.In terms of marketing the products and services owned by the kayon resort, management uses advertisements and uploads them on sosial media owned by the hotel. Various promos and attractive offers were made by the hotel, one of which is Instagram. This research is qualitative research that is described descriptively using advertising data uploaded to sosial media. This study discusses the stylistics and imagery used in the kayon resort advertisements uploaded on sosial media.